ANALISIS TERHADAP PELAKSANAAN DAN DAMPAK KEGIATAN PROJEK PENGUATAN PROFIL PELAJAR PANCASILA (P5) SEBAGAI PENERAPAN KURIKULUM MERDEKA DI SDN 01 SUNGAI RUMBAI - Imelda Adima Putri; Zelhendri Zen; Fetri Yeni; Novrianti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Strengthening Pancasila Student Profile Project (P5) is a project-based co-curricular activity designed to prioritize the achievement of competencies and character development in accordance with the Pancasila Student Profile, which is formulated based on graduate competency standards. This descriptive qualitative study aims to examine the implementation of the P5 Project at SDN 01 Sungai Rumbai, identify the impacts experienced during its execution, and analyze the supporting and inhibiting factors in the project's implementation. The research subjects included the principal, teachers, facilitator team, and students. Data were collected through observations, interviews, and documentation, then analyzed through data reduction, data presentation, and conclusion drawing. The results show that: (1) The P5 Project at SDN 01 Sungai Rumbai was implemented through the